Effects of hormone concentrations on anther cultures and the acquisition of regenerated plants of five awnless triticale genotypes - Jun Ma; Fangyuan Zhao; Yinxia Zhang; Xinhui Tian; Wenhua Du (Plant Methods)
Abstract Background The rapid production of doubled haploids by anther culture technology is an important breeding method for awnless triticale. The aim of this study was to explore the effects of triticale genotype and the types and ratios of exogenous hormones in the medium on the efficiency of triticale anther culture. Results Anthers of five triticale genotypes were cultured on four different callus induction media and the calli were induced to differentiate into green plants by culture on three different differentiation media. The triticale genotype T8004 showed the best performance in anther culture, with a callus induction rate of 28.64%, a green plantlet differentiation frequency of 33.33%, and a green plantlet production rate of 2.78%. The highest callus induction rates were obtained by culturing anthers on C3 medium (the main components were potassium nitrate, glutamine, inositol, etc.), and the highest green plantlet differentiation frequency was obtained by culturing calli on D2 differentiation medium (the main components were potassium nitrate, ammonium nitrate, calcium chloride dihydrate, etc.). Flow cytometry analyses showed that 15 of the 20 DH0 generation plants that grew normally in the field were doubled haploids. The average chromosome doubling success rate was 55.6%. Analyses of agronomic traits showed that the 11 DH1 doubled haploid plants reached the standard for awnless triticale, so they are candidate materials for breeding new awnless triticale varieties. Conclusion The anther culture technology of triticale was optimized in this paper, which made it possible to rapidly breed homozygous varieties of awnless triticale.